Hetero Diels–Alder Chemistry for the Functionalization of Single‐Walled Carbon Nanotubes with Cyclopentadienyl End‐Capped Polymer Strands. Issue 8 (18th March 2013) - Zydziak, Nicolas; Preuss, Corinna M.; Winkler, Volker; Bruns, Michael; Hübner, Christof; Barner‐Kowollik, Christopher
Abstract Single‐walled carbon nanotubes (SWCNTs) are pre‐functionalized with a pyridinyl‐based dithioester to undergo a hetero Diels–Alder (HDA) reaction with cyclopentadienyl end‐capped poly(methyl)methacrylate (<overline>M</overline>n = 2700 g mol−1, PDI = 1.14). Fourier transform infrared spectroscopy, thermogravimetric analysis, elemental analysis (EA), and X‐ray photoelectron spectroscopy (XPS) evidence the success of the grafting process. The estimated resulting grafting density (from XPS and EA) via the HDA reaction increases by a factor of more than two (0.0774 chains·nm−2 via XPS) compared with typical values obtained via a direct cyclopentadiene driven Diels–Alder conjugation onto non‐functional SWCNTs under similar conditions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>